Tata cara sertifikasi pemenuhan aspek cara pembuatan obat tradisional yang baik (CPOTB) bertahap dalam rangka kemudahan bagi usaha mikro kecil (UMK) di Bandung Jawa Barat - Ivanna Fauziyah Kusnadi; Patihul (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Traditional medicine products continue to grow rapidly, both produced by UMOT, UKOT, IOT, IEBA, and the pharmaceutical industry. With the development of the use of traditional medicine, UMK such as UKOT and UMOT are becoming more formed. However, the high number of UMK present was not followed by the fulfillment of provisions related to the inspection of the facilities carried out. Based on the BBPOM Annual Report in Bandung, inspection of UMOT/UKOT facilities was carried out on 21 facilities and 33.33% did not meet the requirements (TMK). One of the results of inspection of facilities that did not meet these requirements was because they did not meet CPOTB aspects, both sanitation hygiene and documentation (42.86%). This can be caused by the lack of awareness of business actors regarding the basics in making a traditional medicinal product starting from the establishment of the facility and also the ignorance of business actors regarding the legal basis that must be adhered to. This article aims to explain the procedure for certifying the fulfillment of CPOTB aspects in order to make it easier for UMK to register their places with Balai POM.